Microwave assisted synthesis and characterisation of trinuclear Zinc(II) schiff base complexes derived from m-phenylenediamine and salicylaldehyde / Karimah Kassim and Muhamad Azwan Hamali - Karimah Kassim; Muhamad Azwan Hamali (Penerbit UiTM (UiTM Press), 2017)
A series of Schiff base ligand, SALMPD, and its mono- and trinuclear Zn(II) metal complexes were synthesised from m-phenylenediamine and salicylaldehyde in alcoholic solution. The synthesis of ligand and mononuclear complex were synthesised using conventional condensation method, while the trinuclear complex was done using microwave-assisted synthesis method. The structure of each compound was elucidated by elemental analysis, infrared and 1H NMR spectroscopy. The infrared spectrum of SALMPD shows a strong azomethine (C=N) band at 1621.62cm-1, indicates the formation of the ligand. Upon complexation of the mononuclear complex, the C=N infrared band shifted and the disappearing of the phenolic hydrogen signal in 1H NMR suggesting the chelation between Zinc(II) metal ion and ligand took place when azomethine and phenolic hydrogen deprotonated. The trinuclear complex, Zn3(SALMPD) obtained was consist of two moieties of mononuclear Zn(SALMPD), which act as ligands that chelating to the third Zn(II) metal ion through oxygen atom due to the shifting of M-O infrared band from 575.12-540.53cm-1, which serves as a coordination site for the metal ion.